(untitled) (Research, Society and Development, 2020)
Objective: to investigate the scientific production about the difficulties faced by lesbians, gays, bisexuals, transvestites, transsexuals and transgender people in public health care. Methodology: a narrative review study was used, based on the guiding question of the research: What are the main barriers / difficulties faced by this public to access public health? Results: a total of 16 publications were found, of which 13 were selected that had their titles related to the proposed theme. Discussion: in the case of the LGBT population, in access to education and health work, discrimination is accentuated because this minority does not fit the standards set by a conservative society. Final Considerations: the access of this population group to public health services is limited, permeated by omission, intolerance, constraints and ethical and excluding positions. Despite strategies to deal with inequities and inequalities, implemented by the Unified Health System, it still requires improvement and, especially, raising the awareness of the professionals who serve this population.